A Mesoarchean Large Igneous Province on the Eastern Kaapvaal Craton (Southern Africa) Confirmed by Metavolcanic Rocks from Kubuta, Eswatini - Schneider, K. P.; Hoffmann, J. E.; Kröner, A.; Balduin, A.; Sprung, P.; Schleicher, A. M.; Münker, C. (Lithosphere, 2022)
Mesoarchean magmatism is widespread on the eastern margin of the Kaapvaal Craton, but its origin is still poorly understood, mainly because geochemical data is rare. To shed some light on the source of this Mesoarchean magmatism and to relate different Mesoarchean volcanic sequences to each other, we provide major and trace element data as well as Hf-Nd isotope compositions of amphibolites sampled close to the Kubuta Ranch in south-central Eswatini. These amphibolites, so far, were of unknown correlation to any volcanic sequence in Eswatini or South Africa. Hence, the aim of our study is to characterize the mantle source composition of these volcanic rocks and, furthermore, to constrain their genetic relation to other volcanic sequences in Eswatini and South Africa. Our findings reveal that, based on coherent trace element patterns and similar Nd isotope characteristics, the Kubuta volcanic rocks can be genetically linked to the ca. 3.0 Ga Usushwana Igneous Complex in West-Central Eswatini and the ca. 2.9 Ga Hlagothi Complex located in the KwaZulu-Natal province. In contrast, the coeval ca. 3.0 Ga Nsuze and ca. 2.9 Ga Mozaan Groups (Pongola Supergroup) of south-central Eswatini and northern KwaZulu-Natal province have slightly enriched compositions compared to the newly sampled Kubuta volcanic rocks. Our results suggest that the Nsuze and Mozaan Groups were sourced from a primitive mantle reservoir, whereas the Usushwana, Hlagothi, and Kubuta mafic rocks were derived by melting of a more depleted mantle source comparable to that of modern depleted MORB. Furthermore, our assimilation-fractional crystallization (AFC) calculations and Nd isotope constraints reveal that some samples were contaminated by the crust and that the crustal contaminants possibly represent felsic rocks related to the ca. 3.5 Ga crust-forming event in the Ancient Gneiss Complex. Alternatively, melting of a metasomatized mantle or plumelithospheric mantle interaction may also produce the trace element and isotopic compositions observed in the samples. From a synthesis of our geochemical observations and age data from the literature, we propose a refined petrogenetic model, for a continental flood basalt setting in a Mesoarchean large igneous province on the eastern Kaapvaal Craton. Our petrogenetic model envisages two magma pulses sourced from a primitive mantle reservoir that led to the formation of the Nsuze (first) and Mozaan (second) lavas. Conductive heating of ambient depleted mantle by the mantle plumes caused partial melting that led to the formation of the Usushwana Igneous Complex associated with the first magmatic event (Nsuze) and the Hlagothi Igneous Complex associated with the second magmatic event (Mozaan). However, due to lacking age data of sufficient resolution, it is not possible to affiliate the Kubuta lavas to either the first or the second magmatic event
CRIS-Team Scopus Importer:2022-03-11